2013
DOI: 10.1371/journal.pone.0061064
|View full text |Cite
|
Sign up to set email alerts
|

Oncomir miR-125b Suppresses p14ARF to Modulate p53-Dependent and p53-Independent Apoptosis in Prostate Cancer

Abstract: MicroRNAs are a class of naturally occurring small non-coding RNAs that target protein-coding mRNAs at the post-transcriptional level and regulate complex patterns of gene expression. Our previous studies demonstrated that in human prostate cancer the miRNA miR-125b is highly expressed, leading to a negative regulation of some tumor suppressor genes. In this study, we further extend our studies by showing that miR-125b represses the protein product of the ink4a/ARF locus, p14ARF, in two prostate cancer cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 38 publications
1
53
0
1
Order By: Relevance
“…Low levels of ARF in prostate cancer (19 -21) were also attributed to androgen-inducible microRNA-125b that negatively regulates ARF in prostate cancer (68). Our studies suggest that low levels of ARF in prostate cancer increase the levels of MAGE-A11 by decreasing MAGE-A11 degradation.…”
Section: Discussionmentioning
confidence: 62%
“…Low levels of ARF in prostate cancer (19 -21) were also attributed to androgen-inducible microRNA-125b that negatively regulates ARF in prostate cancer (68). Our studies suggest that low levels of ARF in prostate cancer increase the levels of MAGE-A11 by decreasing MAGE-A11 degradation.…”
Section: Discussionmentioning
confidence: 62%
“…An example for this may be the apoptotic cell death and p53 networks, which have been shown to be targeted by miR-125b on different levels. 7,21,25,39,40 Accordingly, our data reveal miR-125b-mediated suppression of pro-apoptotic genes Bak1 and Trp53inp1, as well as slightly reduced expression, albeit either not statistically significant or not within our cutoff criteria, in pro-apoptotic Bmf and Bbc3 (BCL2-binding component 3; Puma). Moreover, TNFAIP3, which has been shown to regulate apoptosis under low-serum conditions, was strongly decreased.…”
Section: Figure 4 Identification Of Target Genes Regulated By Mir-125mentioning
confidence: 57%
“…miR-125b has been observed to be downregulated in various types of cancer, including oral cancer (23), bladder cancer (18), liver cancer (19), osteosarcoma (20) and endometrial cancer (24). Previous studies have also demonstrated that miR-125b was upregulated in a number of types of cancer, including prostate cancer (25), glioblastoma (26) and pediatric acute promyelocytic leukemia (27). However, there are no studies investigating the expression of miR-125b in LSCC.…”
Section: Discussionmentioning
confidence: 99%